Persepsi Guru Kimia dan Siswa Kelas XI MIPA SMAN 1 dan SMAN 2 Labuapi Terhadap Lembar Kerja Peserta Didik Bermuatan Etnosains Pada Materi Pokok Koloid - Ariana, Lisa; Andayani, Yayuk; Rahmawati, Rahmawati (FKIP University of Mataram, 2024)
This study aims to describe the perceptions of teachers and students of class XI MIPA towards ethno-science-laden worksheets on the subject matter of colloids, This research is a descriptive research with a quantitative approach. The research population was chemistry teachers and students of class The sampling method was obtained using a saturated sampling technique. Teacher perception data is reviewed from 4 aspects, namely technique. Teacher perception data is reviewed from 4 aspects, namely technical, content, construct and ethnoscience, while student perception data is reviewed from 2 factors, namely internal factors and external factors. Data on teacher and students perceptions of ethnosciensce laden LKPD was collected using a closed questionnaire with a Likert scale. The descriptive statisticalanalysis technique used is in the form of the research show that teachers perceptions of all aspects in very good criteria with an average for technical aspects, construct content, ethnoscience of 91% , 83%, 87%, and 86%, while students perceptions of all factors are in good criteria with averages. Average on internal factors 82%, 82%, 81%, while external factors 83%, and 84%. Based on these results, it was concluded that the ethnoscience-laden LKPD which integrated jeleng oil into the subject matter of colloids was suitable for use in the learning process.